The HLA locus contains novel foetal susceptibility alleles for congenital heart block with significant paternal influence. (20th January 2014) - Meisgen, S.; Östberg, T.; Salomonsson, S.; Ding, B.; Eliasson, H.; Mälarstig, A.; Alfredsson, L.; Klareskog, L.; Hamsten, A.; Olsson, T.; Axelsson, T.; The Swedish Congenital Heart Block Study Group; et al.
Abstract Objective The main aim of this study was to identify foetal susceptibility genes on chromosome six for Ro/SSA autoantibody‐mediated congenital heart block. Subjects and Design Single nucleotide polymorphism (SNP) genotyping of individuals in the Swedish Congenital Heart Block (CHB) study population was performed. Low‐resolution HLA‐A, ‐Cw and ‐DRB1 allele typing was carried out in 86 families comprising 339 individuals (86 Ro/SSA autoantibody‐positive mothers, 71 fathers, 87 CHB index cases and 95 unaffected siblings). Results A case–control comparison between index cases and population‐based out‐of‐study controls (n = 1710) revealed association of CHB with 15 SNPs in the 6p21.3 MHC locus at a chromosome‐wide significance of P < 2.59 × 10−6 (OR 2.21–3.12). In a family‐based analysis of association of SNP markers as well as distinct MHC class I and II alleles with CHB, HLA‐DRB1*04 and HLA‐Cw*05 variants were significantly more frequently transmitted to affected individuals (P < 0.03 and P < 0.05, respectively), whilst HLA‐DRB1*13 and HLA‐Cw*06 variants were significantly less often transmitted to affected children (P < 0.04 and P < 0.03). We further observed marked association of increased paternal (but not maternal) HLA‐DRB1*04 transmission to affected offspring (P < 0.02). Conclusions HLA‐DRB1*04 and HLA‐Cw*05 were identified as novel foetal HLA allele variants that confer susceptibility to CHB in response to Ro/SSA autoantibody exposure, whilst DRB1*13 and Cw*06 emerged as protective alleles. Additionally, we demonstrated a paternal contribution to foetal susceptibility to CHB for the first time.